1994
DOI: 10.1155/s1064744994000219
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Tissue: To Suture or Not to Suture at Cesarean Section

Abstract: Objective: The null hypothesis for this investigation was that there was no difference in the frequency of wound disruption between women who had their subcutaneous tissues approximated with suture and those who did not during cesarean section. Methods: During alternating months, consecutive women delivered by cesarean section either did (N = 716) or did not (N = 693) have their subcutaneous tissues closed with suture. All data were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Several interventions to reduce wound complications have been assessed, including pre-surgical antibiotic treatment and surgical site preparation,[2, 12] maintenance of normothemia, [13, 14] subcutaneous drain placement or suture closure, [1520] subcuticular skin closure,[2124] retention sutures,[25] wound protection devices,[26] negative pressure dressings[27] and skin sealants. [28] The results of these studies have been conflicting; many limited to obstetrical patients or have used varying definitions of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Several interventions to reduce wound complications have been assessed, including pre-surgical antibiotic treatment and surgical site preparation,[2, 12] maintenance of normothemia, [13, 14] subcutaneous drain placement or suture closure, [1520] subcuticular skin closure,[2124] retention sutures,[25] wound protection devices,[26] negative pressure dressings[27] and skin sealants. [28] The results of these studies have been conflicting; many limited to obstetrical patients or have used varying definitions of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bohman et al . reported that wound disruption was found in 7.7% of 1184 women with vertical incision as opposed to 2.2% of 225 women with a Pfannenstiel incision ( P = 0.004) . As with the present investigation, Cetin and Cetin included only the transverse skin incision in their study and analyzed their cohort in two subgroups as women with a subcutaneous fat thickness less than 2 cm and more than 2 cm .…”
Section: Discussionmentioning
confidence: 78%
“…reported that a high preoperative hematocrit level was protective and the factors associated with wound complications included vertical skin incisions and endometritis . Furthermore, obesity, non‐sutured closure, four or more vaginal examinations and high body mass index were recorded as significant factors for wound disruption …”
Section: Discussionmentioning
confidence: 99%
“…19 In a subsequent investigation, Bohman and coworkers conducted a prospective controlled trial (level 1 evidence) comparing outcomes in 716 women who had a deep subcutaneous closure with outcomes in 963 women who had no closure. 20 In women who had closure of the subcutaneous layer, the rate of wound disruption was reduced by 32%. Finally, in an excellent meta-analysis, Chelmow et al reviewed three studies that included 875 patients.…”
Section: Close the Uterine Incision In Two Layers Rather Than Onementioning
confidence: 99%